ON THE DESIGN OF ROBUST 2 DEGREE OF FREEDOM CONTROLLERS - Limebeer, D; Kasenally, E; Perkins, J (1993)
The aim of this paper is to introduce two methods of designing robust two degree of freedom (TDF) controllers. Both design procedures will be illustrated and evaluated on a high purity distillation column example. In the first approach the feedback controller and the prefilter are designed in a single step using an H∞ optimization procedure. The second method optimizes the feedback controller and prefilter in two separate design stages. Roughly speaking, the feedback controller is designed to meet robust stability and disturbance rejection specifications, while the prefilter is used to improve the robust model matching properties of the closed loop system. The single step approach has the advantages that it is easy to use, and that the resulting controller degree is the same as that of the plant. The two stage approach offers greater design flexibility and it may produce robust stability and robust performance margins which are significantly bigger than those achievable with the single stage approach. Set against that, the two stage technique is more difficult to use and it produces controllers which may have an order which is significantly bigger than that of the plant. © 1992.